Grammatical and semantic features of English idioms denoting negation with reference to their Vietnamese equivalents / Nguyễn Thị Hằng; Supervisor: PGS.TS Nguyễn Đăng Sửu - Nguyễn, Thị Hằng
This thesis attempts to investigate grammatical and semantic features of English idioms and provervs denoting negation with reference to the Vietnamese equivalents. The study is implemented via the adoptions of descriptive and contrastive, inductive, and deductive methods. The investigation is based on 252 samples of English idioms and provervs denoting negation with reference to the Vietnamese equivalents from a wide variety of dictionaries and websites about idioms. The findings are compared and contrasted to reveal the outstanding similarities and differences between English idioms and provervs denoting negation and their Vietnamese equivalents in terms of grammatical and semantics. Additionally, some suggested implications will help me teach students how to learn and use idioms and provervs denoting negation in social situation.